The Language of Business E-Mail: An Opportunity to Bridge Theory and Practice - Julio C. Gimenez (Scripta Manent, 2015)
The language of business email has attracted a great deal of attention in the last decade. Research studies on the language, style and register of business email have been published in many journals, books and other publications. However, many of these discussions have been theoretical in nature, failing to make a connection between theory and practice. It is then the task of the ESP teacher to make such a connection. This article argues that business communication lends itself well to bringing theory and practice closer together. To this end, the article first identifies relevant features which have started to emerge from main studies in the language of business email, a vital component in business communication. It then explores different possible pedagogical applications of these findings in the BE class. The article discusses the SAE (Selecting, Applying and Evaluating) model which can be used to design and evaluate classroom activities. The article finally presents four activities which have been created following the main findings emerging from the research reviewed.